Measurement of the energy density as a function of pseudorapidity in proton-proton collisions at root s=13 TeV - Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Ambrogi, F.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Dragicevic, M.; Eroe, J.; Del Valle, A. Escalante; Flechl, M.; Fruehwirth, R.; et al. (Springer, 2019)
A measurement of the energy density in proton-proton collisions at a centre-of-mass energy of sTeV is presented. The data have been recorded with the CMS experiment at the LHC during low luminosity operations in 2015. The energy density is studied as a function of pseudorapidity in the ranges -6.6<<-5.2 and 3.15<

<5.20. The results are compared with the predictions of several models. All the models considered suggest a different shape of the pseudorapidity dependence compared to that observed in the data. A comparison with LHC proton-proton collision data at s=0.9 and 7 TeV confirms the compatibility of the data with the hypothesis of limiting fragmentation.